HARDWARE AND SOFTWARE AND APPLICATION OF UNMANNED AIRCRAFT - SAVCHENKO, YAROSLAV; YAHODZINSKYI, SERHII; LYTVYNENKO, LEONID; SUSHYNSKYI, OREST (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Unmanned aerial vehicles (UAVs), or drones, have gained significant popularity in civilian society due to their versatility and wide range of capabilities. Previously used primarily for military purposes, today drones have found applications in many industries, including agriculture, construction, environmental monitoring, logistics, healthcare, and entertainment. They are capable of a variety of tasks, from aerial photography and mapping to monitoring farmland and delivering goods. With the ability to perform complex operations autonomously or under the control of an operator, UAVs have become indispensable tools in many professional fields. Flight controllers such as the Navio 2 play a key role in stabilizing and controlling flight. Navio 2, being an expansion board for Raspberry Pi, provides full flight controller functionality. They integrate various sensors, including GPS, accelerometers and gyroscopes, which allows for accurate positioning and flight stability. These controllers allow the drone to perform autonomous missions, follow set trajectories and maintain a stable position in the air.Engine speed governors control the speed of rotation of the engines, which ensures a smooth and stable flight. Prospects for further exploration also include the integration of UAVs with other technologies, such as artificial intelligence and the Internet of Things (IoT), which will allow the creation of even more autonomous and intelligent systems. For example, the use of artificial intelligence can improve drones' ability to make autonomous decisions in complex situations, and integration with the IoT will allow large networks of drones to be more efficiently managed for coordination tasks.
Keywords: unmanned aerial vehicles; drones; types of UAVs; multicopters; UAV applications; quadcopters; flight controllers; autonomous flight; video recording; engine speed controllers